Hutu rebels : exile warriors in the eastern Congo - Hedlund, Anna (Ethnography of political violence., 2020)
Drawing on ethnographic fieldwork in a rebel camp located deep in the Congo forest, Anna Hedlund explores the micropolitics and practices of everyday life in a community of Hutu rebel fighters and their families and attempts to understand why they continue to fight in what appears to be an endless conflict.